Cancer-Related Decision-Making Among Adolescents, Young Adults, Caregivers, and Oncology Providers. (November 2021) - Darabos, Katie; Berger, Allison J.; Barakat, Lamia P.; Schwartz, Lisa A.
Decision-making among adolescents and young adults with cancer (AYA) is often complex, ongoing, and multifaceted, involving caregiver and oncology provider perspectives. Engagement in decision-making against the backdrop of normative developmental processes of acquiring autonomy and gaining independence contributes to the complexity of decision-making. Semi-structured qualitative interviews from 11 AYA and caregiver dyads and eight oncology providers examined decision-making processes with specific attention to the role of shared decision-making, cognitive and emotional processes, and coping with the decision-making experience. Five decision-making patterns were identified, with collaborative decision-making and AYA-driven decisions most commonly described. Utilizing hypothesis coding, AYA and caregivers explained how cognitive (i.e., pros/cons) and emotional (i.e., shock and fear of missing out) processes influenced cancer-related decisions. Coping strategies provided clarity and respite when engaged in decision-making. Our findings illuminate important implications for how to best support decision-making among AYA and caregivers, including the role oncology providers can play during decision-making.